Aerodynamic wake oscillator for modeling flow-induced vibration of tandem cylinders with short spans. (15th August 2021) - Fan, Xiantao; Wang, Yang; Tan, Wei
Abstract: The tandem cylinders immersed in an oncoming flow undergo violent flow-induced vibration (FIV). The cylinders with short spans, in the specific conditions of airflow and mass damping, experience the galloping-like but self-limited vibration. It promotes a coupling instability, controlled by the shear layers and wake vortices. The peculiar behavior of FIV for tandem cylinders is the interference between transverse galloping and vortex-induced vibration (VIV), which lacks a modeling approach through classical theories. Based on the quasi-steady assumptions, a mathematical model including two semicoupled structural oscillators and a reduced wake oscillator was established to simulate the vibration responses. A nonlinear aerodynamic damping coefficient and an empirical interfered force were introduced to the model, revealing the unexplored interference mechanism between two cylinders with short spans. The model with calibrated parameters can reproduce the nonlinear and bifurcated vibration responses of cylinders, providing a quantitative agreement with the experimental data. Although the model only works for high Scruton numbers and loses high fidelity in predicting the vibration amplitudes of the downstream cylinder in several cases, the vital velocity thresholds, amplitude-velocity trends and maximum amplitudes can be precisely obtained. This model is conducive to preacquiring the FIV responses of tandem industrial structures, including steel stacks, bladeless wind turbines, low-power energy-harvesting devices, etc. Graphic abstract: Image, graphical abstract Highlights: Aerodynamic wake oscillator was proposed for modeling FIV of tandem cylinders. A nonlinear aerodynamic damping coefficient K was introduced to this model. FIV of tandem cylinders shows nonlinear and bifurcation features. The model can provide a quantitative agreement with the experimental data. The velocity threshold, amplitude-velocity trend and maximum amplitude are modelled.